First record of Ulex europaeus (Fabaceae, Faboideae) in Mexico - Mosso-Mancilla, Enrique; Lezama-Sánchez, Fernanda; Castillo-Gutiérrez, Antonio; Flores-Tolentino, Mayra; Tovar-Sánchez, Efraín; Ramírez-Rodriguez, J. Rolando (Instituto de Ecología, A.C., 2022)
Background and Aims: The species Ulex europaeus (Fabaceae, Faboideae) has been listed as one of the 100 most harmful invasive species worldwide. It is native to western Europe and northwestern Africa, and has become naturalized throughout Europe and the Middle East. Its environmental and economic impact in America is documented in Canada, Chile, Colombia and the United States of America. It is found at different altitudes and in vegetation types. This study aims to contribute to the knowledge of the distribution of Ulex europaeus in the Mexican territory, as a basis for immediate actions regarding its control and eradication. Methods: Botanical material was collected in the temperate forest of the community of Tres Marías, municipality Huitzilac, in the state of Morelos, Mexico. Dichotomous keys and botanical descriptions were used for taxonomic determination. An exhaustive review of specialized literature was carried out, images were consulted, and data were obtained from virtual herbaria around the world, and the herbaria MEXU and UAMIZ were visited for consultation. The field work in the state of Morelos was supported by ArcGIS projections. The collected material is deposited in the collection of the herbarium HUMO of the Autonomous University of the State of Morelos. Key results: The authors register for the first time, by means of botanical collections, the presence of U. europaeus in Mexico. Supported by field trips and the review of various sources of information, so far only a population of 63 individuals of this species has been found. The phenology of the species coincides with that reported for other latitudes Conclusions: This record broadens the distribution range of U. europaeus. The presence of this species adds to the real and potential factors that are affecting the biodiversity of our country. It is necessary to establish strategies, control actions and eventual eradication of this invasive species.